2021
DOI: 10.1038/s41372-021-01119-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute kidney injury in neonates with congenital diaphragmatic hernia

Abstract: Objective To examine incidence of acute kidney injury (AKI), antenatal and postnatal predictors, and impact of AKI on outcomes in infants with congenital diaphragmatic hernia (CDH). Study design Single center retrospective study of 90 CDH infants from 2009–2017. Baseline characteristics, CDH severity, possible AKI predictors, and clinical outcomes were compared between infants with and without AKI. Result In total, 38% of infants developed AK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
2
10
3
1
Order By: Relevance
“…A previously reported study had shown an increased incidence of AKI in CDH infants receiving vancomycin [ 6 ]. While previous studies have shown that gentamicin exposure is associated with AKI in infants with CDH [ 5 , 6 ], our study showed no significant difference. This is may be because all the infants received gentamicin as first line antibiotic in our institution.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…A previously reported study had shown an increased incidence of AKI in CDH infants receiving vancomycin [ 6 ]. While previous studies have shown that gentamicin exposure is associated with AKI in infants with CDH [ 5 , 6 ], our study showed no significant difference. This is may be because all the infants received gentamicin as first line antibiotic in our institution.…”
Section: Discussioncontrasting
confidence: 98%
“…Our study found that ionotrope administration, sepsis, day of surgery or patch repair was not associated with increased incidence of AKI. This was similar to findings from the previous studies [ 5 , 8 ]. Ryan et al found that inotrope administration and sepsis did not affect the incidence of AKI, but patch repair was associated with an increased incidence of AKI [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations